2016
DOI: 10.1523/jneurosci.3254-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

BAZ1B in Nucleus Accumbens Regulates Reward-Related Behaviors in Response to Distinct Emotional Stimuli

Abstract: ATP-dependent chromatin remodeling proteins are being implicated increasingly in the regulation of complex behaviors, including models of several psychiatric disorders. Here, we demonstrate that Baz1b, an accessory subunit of the ISWI family of chromatin remodeling complexes, is upregulated in the nucleus accumbens (NAc), a key brain reward region, in both chronic cocaine-treated mice and mice that are resilient to chronic social defeat stress. In contrast, no regulation is seen in mice that are susceptible to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 45 publications
1
42
0
Order By: Relevance
“…For example, chronic cocaine exposure results in increased expression of the bromodomain and extraterminal protein BRD4, an epigenetic reader protein (41), and PSMC5, an ATPase-containing subunit of the 19s proteasomal complex (42). We recently demonstrated that an accessory ATPase subunit of the ISWI family of chromatin remodeling complexes, bromodomain adjacent to zinc finger domain 1B, is also upregulated in the NAc (22). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, chronic cocaine exposure results in increased expression of the bromodomain and extraterminal protein BRD4, an epigenetic reader protein (41), and PSMC5, an ATPase-containing subunit of the 19s proteasomal complex (42). We recently demonstrated that an accessory ATPase subunit of the ISWI family of chromatin remodeling complexes, bromodomain adjacent to zinc finger domain 1B, is also upregulated in the NAc (22). …”
Section: Discussionmentioning
confidence: 99%
“…Self-administration procedures were conducted as previously described (11, 21, 22). Following the 7 d recovery from jugular catheter surgery, rats were assigned to self-administer either saline or 1.0 mg/kg/inf cocaine.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was isolated from the NAc of individual mice and qRT-PCR was performed as described previously (Sun et al, 2015, Sun et al, 2016). Briefly, bilateral 14 gauge punches of NAc were obtained at varying times after the last cocaine or saline injection and frozen on dry ice until further use.…”
Section: Methodsmentioning
confidence: 99%
“…ATP–dependent chromatin remodelers also play an important role in regulating gene expression by altering nucleosome positioning, and have been implicated in modulating learning and memory behaviors as well as regulating reward-related behaviors in animal models of depression and drug addiction (Whitehouse et al, 2007, Clapier and Cairns, 2009, Yen et al, 2012, Narlikar et al, 2013, Vogel-Ciernia et al, 2013, Sun et al, 2015, Sun et al, 2016). Specifically, the persistent induction of BAZ1A, an accessory subunit of the ISWI family of chromatin remodeling proteins, has been shown to be important in mediating repeated stress-induced depressive-like behaviors through nucleosome repositioning in NAc (Sun et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To my knowledge, only one other study has examined CRCs in cocaine-related behaviors. Sun et al found that overexpression of Baz1b, an accessory subunit of the imitation switch family of CRCs, drives potentiation of cocaine reward during self-administration in mice, and also confers resilience to chronic social defeat stress (8). …”
mentioning
confidence: 99%